Design of steel and concrete composite beams according to NBR8800:2008 using pygad genetic algorithm and python implementation - de Lima Bastos, Paula Cristina; Neves, Francisco de Assis das; Fernandes, Walliston dos Santos (REM - International Engineering Journal, 2025)
Abstract In this article presents a programming routine that was developed based on the Python language for the design of non-slender web steel beams having mono symmetrical and doubly symmetrical sections, with welded and rolled profiles, and composite steel and concrete beams, in accordance with NBR8800:2008 for various loads. A Genetic Algorithm routine was incorporated into the code in order to perform discrete parametric optimization to obtain the best profile from an extensive list of commercial profiles for a given load. Important parameters, such as bending inertia, weight, elastic modulus, radius of gyration and simple bending were used in a weighting function, consisting of a linear combination of these parameters and weights. After determining the optimum weights of the weighting function via the PyGad genetic algorithm, the optimized profile was found to meet the constraints prescribed by the NBR8800:2008 standard. Between the serviceability limit states, vibration frequency checks were inserted into the optimization problem. Finally, following the optimization process, the designed and optimized elements will be checked for dynamic susceptibility through modal analysis. After checking the design constraints, according to NBR8800:2008, various analyses can be carried out with the selected beam, such as price, weight ratio, boundary condition, use and even a parallel study between various types of beams and profiles of different models. In this way, seven different beam models were made for comparison, showing that the program can be effective for future studies or even for day-to-day practice.